Consumer’s satisfaction towards Goods and Services Tax (GST) implementation on agro-based products - Muhamad, Nur Aminin (2018)
Starting April 2015, Goods and Service Tax (GST) in Malaysia was effective. However, the society have developed negative perception after the implementation of GST as the price hike. Nevertheless, society need to accept as it is a regulation that have been stated by government. General objective of this study is to identify the consumers’ satisfaction towards GST implementation on agro-based products while the specific objectives are to study the association between socio-demographic and consumers’ satisfaction towards GST implementation on agro-based products; to investigate the factors that influence the confirmation for consumers to satisfy with GST implementation on agro-based products; to investigate the relationship between expectation of consumer towards GST implementation on agro-based products and performance of GST implementation on agro-based products towards confirmation for consumers to satisfy with GST implementation on agro-based products; and to investigate the relationship between confirmation for consumers to satisfy with GST implementation on agro-based products and consumers’ satisfaction towards GST implementation of agro-based products. The survey have been conducted on 400 respondents in Hulu Selangor and Petaling. Descriptive analysis, chi-square analysis, factor analysis and regression analysis were used. Results show that there is an association between socio-demographic and consumers’ satisfaction towards GST implementation on agro-based products; the factors that influence confirmation for consumers to satisfy with GST implementation on agro-based products are performance of GST implementation on agro-based products followed by expectation of consumer towards GST implementation on agro-based products; the performance of GST implementation on agro-based products have stronger relationship with confirmation for consumers to satisfy with GST implementation on agro-based products compared to expectation of consumer towards GST implementation on agro-based products; and there are strong relationship between confirmation for consumers to satisfy with GST implementation on agro-based products and consumers’ satisfaction towards GST implementation on agro-based products. Recommendation for this study are GST should be implemented considering to consumers’ income and residential area; special provision should be provided towards low income earners; violation regarding to transparency of GST should be avoided; and there should be constant improvement of economic achievement.